2020
DOI: 10.3389/fnhum.2020.00321
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Motor Imagery Performance From Resting-State EEG Using Dynamic Causal Modeling

Abstract: Motor imagery-based brain–computer interfaces (MI-BCIs) send commands to a computer using the brain activity registered when a subject imagines—but does not perform—a given movement. However, inconsistent MI-BCI performance occurs in variations of brain signals across subjects and experiments; this is considered to be a significant problem in practical BCI. Moreover, some subjects exhibit a phenomenon referred to as “BCI-inefficiency,” in which they are unable to generate brain signals for BCI control. These s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 76 publications
(116 reference statements)
2
41
0
Order By: Relevance
“…Future research should look into other EEG measures that account for BCI aptitude and performance. For instance, recent studies have proposed that connectivity measures can uncover the underlying brain activity in (in-)efficient users (Lee et al, 2020) and that coherence measures can improve accuracy for inefficient users as compared to CSP-dependent classifiers (Zhang et al, 2019). In addition, Nierhaus et al (2019) showed that functional connectivity in the brain networks increased already after 1 h of BCI training.…”
Section: Future Researchmentioning
confidence: 99%
“…Future research should look into other EEG measures that account for BCI aptitude and performance. For instance, recent studies have proposed that connectivity measures can uncover the underlying brain activity in (in-)efficient users (Lee et al, 2020) and that coherence measures can improve accuracy for inefficient users as compared to CSP-dependent classifiers (Zhang et al, 2019). In addition, Nierhaus et al (2019) showed that functional connectivity in the brain networks increased already after 1 h of BCI training.…”
Section: Future Researchmentioning
confidence: 99%
“…The next aspect refers to the assessment of resting-state activation on a reduced number of electrodes. To this end, we evaluate the DRN performance for the predictor sets extracted over the sensorimotor area, selecting the following electrodes, as suggested in [ 44 ]: (FC1, FC2, FC3, FC4, FC5, FC6, Cz, C1, C2, C3, C4, C5, C6, CPz, CP1, CP2, CP3, CP4, CP5, and CP6). In Table 5 , the lower part of each database presents the assessments computed for the sensorimotor zone (denoted with ⋆ ), showing that the channel selection strategy also improves the performance of every subject partition compared to the corresponding values in Table 4 obtained by the whole set of individuals.…”
Section: Resultsmentioning
confidence: 99%
“…Then, the coefficient of determination (noted as R ) is computed. Besides, a p -value is computed from a two-sided t-test whose null hypothesis is that the regression slope is zero [ 44 ]. It is worth noting that such a hypothesis testing is used, as in state-of-the-art works [ 38 , 44 ], because our Deep Learning Regressor aims to code the no consistency in the brain patterns among different subjects to favor a linear dependency between and .…”
Section: Experimental Set-upmentioning
confidence: 99%
See 2 more Smart Citations